Economic policy uncertainty and corporate innovation-empirical evidence from Chinese pharmaceutical listed companies - Wu, Zikun; Wang, Su; Kuang, Licong; Chen, Yuwen (Frontiers in Public Health, 2024)
IntroductionUnder the background that economic policy uncertainty tends to be normal, the innovation behavior of enterprises can cope with the cost impact brought by economic policy uncertainty.MethodsBased on the relevant data of China’s A-share pharmaceutical listed companies from 2015 to 2022, this paper empirically studied the relationship between economic policy uncertainty and firm innovation by using fixed-effect model, intermediary model, instrumental variable method and two-step method, and investigated the mechanism effects of financialization, executive compensation and government subsidies.ConclusionEconomic policy uncertainty significantly increases the innovation intensity of enterprises. Enterprises with dual management, overseas background and non-state-owned ownership will increase their innovative behavior in the face of economic policy uncertainty. Further analysis shows that economic policy uncertainty increases the innovation intensity of enterprises through three mechanisms: increasing financial transformation, obtaining government subsidies and motivating management. Increasing the innovation intensity of enterprises can deal with the risk impact caused by economic policy uncertainty, but can not deal with the negative impact of cost increase. The transformation of financialization can help enterprises cope with the operational risks and later costs caused by economic policy uncertainty.DiscussionThis study provides empirical evidence for the theoretical inference that firms respond to the impact of economic policy uncertainty and thus increase their innovation behavior.